Traveling Waves in the Underdamped Frenkel–Kontorova Model - Hengyan Li; Shaowei Liu (Discrete Dynamics in Nature and Society)
This paper studies a damped Frenkel–Kontorova model with periodic boundary condition. By using Nash–Moser iteration scheme, we prove that such model has a family of smooth traveling wave solutions.